PERKEMBANGAN LEMBAGA KEUANGAN SYARIAH DI INDONESIA DAN TANTANGANNYA DI ERA DIGITAL - Witri Febriani Panggabean; T. Rahmah Rindiyani; Ahmad Wahyudi Zein (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The development of Islamic financial institutions in Indonesia has shown significant growth in recent years. This growth is marked by the increasing number of Islamic financial institutions, the variety of products and services offered, and the growing public interest in financial systems based on Islamic principles. On the other hand, the advancement of digital technology has brought major changes to the financial sector, including Islamic financial institutions. This study aims to analyze the development of Islamic financial institutions in Indonesia and identify the various challenges they face in the digital era. The method used in this study is a literature review by examining various relevant journals, books, and scientific sources. The results indicate that digitalization provides opportunities for Islamic financial institutions to improve service quality, expand market reach, and enhance operational efficiency. However, several challenges remain, including the low level of public literacy regarding Islamic finance, competition with conventional financial institutions, data security and digital transaction risks, and the need for competent human resources in both technology and Islamic finance.